Vida e medo: concepções de corpo e sexualidade na tradição cristã-católica (Life and fear: conceptions of the body and sexuality in Christian tradition-Catholic) - DOI: 10.5752/P.2175-5841.2011v9n21p284 - Lemos, Carolina Teles (2011)
Our questions refer to the connection among existing body and sexuality conceptions in different moments of Christian-catholic history as well as to the place occupied by those conceptions within a broader culture, establishing a parallel to historic periods. We face a few connected links that remain strongly interacted among themselves such as: life, death, fear and sin. In order to accomplish our analyses we rely on the thoughts of authors that have shown the meanings of body and sexuality as cultural constructions. Through the available literature we search to verify how fear of death, recognized as a characteristic of human nature, is expressed in the conceptions of body and sexuality shown by Christian-catholic tradition; also how this fear is perceived today and how it reflects upon the conceptions of body and sexuality nowadays. The research pointed to the conclusion that one of the possible reasons why Christianity-Catholicism invests so much energy in the control of sexuality and the body is that this represents an area of confrontation of fear of death. Such design is echoed in the wider culture, leading people to join, albeit partially, for so long, the ideal Christian-Catholic control of sexuality and the body.
Pergunta-se pelo elo de ligação entre as concepções de corpo e de sexualidade presentes em diferentes momentos da história do cristianismo-catolicismo e o lugar ocupado pelo corpo e pela sexualidade na cultura mais ampla, em períodos históricos paralelos. Descobriu-se, então, alguns elos de ligação que, por sua vez, estão fortemente interligados entre si: vida, morte, medo, pecado. Para realizar a análise de tal fenômeno, utilizou-se o pensamento de autores que tinham apresentado os significados do corpo e da sexualidade como construções culturais; buscou-se verificar, a partir da literatura disponível: como o medo da morte, que é um dado da natureza humana, se expressa nas concepções de corpo e de sexualidade apresentadas pela tradição cristã-católica; como se percebe esse medo hoje e como ele repercute nas concepções de corpo e de sexualidade na atualidade. A investigação apontou para a conclusão de que um dos possíveis motivos pelos quais o cristianismo-catolicismo investe tanta energia no controle da sexualidade e do corpo é que este representa um espaço de enfrentamento do medo da morte. Tal concepção encontra eco na cultura mais ampla, levando as pessoas a aderirem, ainda que parcialmente, por tanto tempo, o ideário cristão-católico de controle da sexualidade e do corpo.
Keywords: Catholicism; Fear; Sexuality; Body; Catolicismo; Medo; Sexualidade; Corpo